Projeto e implementação de um transformador monofásico com enrolamento terciário - Silva, César Luiz Rodrigues da (2019)
This work presents the design and implementation of a single-phase tertiary winding transformer without central tap. Initially, a study on transformers was conducted, discussing their main constructive aspects, operation, losses and one of their design methods. The transformer design is performed through an algorithm created in computational language. Then, the processes used for implementing the designed transformer are presented. Finally, tests are performed that compare the implemented transformer with the design specifications.